Effect of transcutaneous auricular vagal nerve stimulation on the fatigue syndrome in patients with gastrointestinal cancers — FATIVA: a randomized, placebo-controlled pilot study protocol - Mortimer Gierthmuehlen; Nadine Höffken; Nina Timmesfeld; Kirsten Schmieder; Anke Reinacher-Schick (Pilot and Feasibility Studies, 2023)
Abstract Background Cancer-related fatigue (CRF) is defined as a “distressing, persistent, subjective sense of physical, emotional, and/or cognitive tiredness or exhaustion related to cancer or cancer treatment that is not proportional to recent activity and interferes with usual functioning.” CRF is frequently observed in cancer patients even before the initiation of tumor therapy. Its cause is not clear, but in addition to primary effects of therapy, a tumor-induced elevated level of inflammatory cytokines may play a role. Transcutaneous auricular vagal nerve stimulation (taVNS) is a noninvasive way to activate central nervous pathways and modulate pain perception and the immune system. It has positive effects on autoimmune conditions and can also improve fatigue associated with Sjogren’s syndrome. It is the main purpose of this feasibility study to investigate the feasibility of daily taVNS against CRF. Therefore, the stimulation protocol of the newly introduced smartphone app of the manufacturer is evaluated. Additionally, the effect taVNS on CRF and quality of life (QoL) shall be evaluated. Methods Thirty adult patients with gastrointestinal tumors during or after treatment, relevant CRF (Hornheide questionnaire) and life expectancy > 1 year, are enrolled. Patients are randomized to treatment or sham arm and be informed that they will either feel the stimulation or not. Treatment group will receive left-sided tragus above-threshold stimulation with 25 Hz, 250 µs pulse width, and 28-s/32-s on/off paradigm for 4 h throughout the day for 4 weeks. Sham group will receive no stimulation via a nonfunctional electrode. A daily stimulation protocol with time and average intensity is automatically created by a smartphone app connected to the stimulator via Bluetooth®. Multidimensional Fatigue Inventory-20, Short-Form 36 and Beck Depression Inventory questionnaires will be filled out before and after 4 weeks of stimulation. Discussion Primarily, the patients’ daily stimulation time and intensity will be evaluated through the electronic protocol after 4 weeks. Secondarily, the effect of taVNS on cancer-related fatigue and QoL will be measured through the questionnaires. As taVNS seems to modulate inflammatory cytokines, this noninvasive method may — if accepted by the patients — be a promising adjunct in the treatment of cancer-related fatigue. Trial registration The study was approved by local ethics committee (21–7395) and registered at the DRKS database (DRKS00027481).